2019
DOI: 10.31234/osf.io/kudj3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic internal states shape memory retrieval

Abstract: Why do we sometimes easily retrieve memories, but other times appear to forget them? We often look to our external environment for retrieval cues, but another way to optimize memory retrieval is to be in a mental state, or mode, that prioritizes access to our internal representation of the world. Such a ‘retrieval mode’ was proposed by Endel Tulving (1983), who considered it a neurocognitive state in which one keeps the goal of memory retrieval in mind. Building on Tulving’s proposal, we review converging evid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These findings are consistent with earlier models of PFChippocampal activations during retrieval which posited that frontal cortex guided memory search to enable hippocampally-mediated recovery of memory. (Moscovitch, 1989(Moscovitch, , 1992Burgess & Shallice, 1996;Moscovitch & Winocur, 2002;Gilboa, Winocur, et al, 2006;Gilboa, Alain, et al, 2006), Examining retrieval data from confabulation patients with vmPFC lesions, Moscovitch and Melo (1997) noted that the most prominent deficit in retrieving old autobiographical and historical memories to verbal cues was failure to recover any memory at all, indicative of the crucial role that vmPFC played in initiating retrieval and guiding search (see also Schnider, 2013;Gilboa & Moscovitch, 2017;Gilboa & Marlatte, 2017; see also work on frontal involvement in "retrieval mode", Tulving, 1983;Lepage, Ghaffar, Nyberg, & Tulving, 2000;Tarder-Stoll, Jayakumar, Dimsdale-Zucker, Günseli, & Aly, 2020). The data from the current study, and from that of McCormick et al (2020) suggest that the temporal sequence of PFC-hippocampal activations can vary by the age of the memory and by reminders, but the underlying factors that influence it have yet to be determined.…”
Section: Neuroimaging Resultsmentioning
confidence: 99%
“…These findings are consistent with earlier models of PFChippocampal activations during retrieval which posited that frontal cortex guided memory search to enable hippocampally-mediated recovery of memory. (Moscovitch, 1989(Moscovitch, , 1992Burgess & Shallice, 1996;Moscovitch & Winocur, 2002;Gilboa, Winocur, et al, 2006;Gilboa, Alain, et al, 2006), Examining retrieval data from confabulation patients with vmPFC lesions, Moscovitch and Melo (1997) noted that the most prominent deficit in retrieving old autobiographical and historical memories to verbal cues was failure to recover any memory at all, indicative of the crucial role that vmPFC played in initiating retrieval and guiding search (see also Schnider, 2013;Gilboa & Moscovitch, 2017;Gilboa & Marlatte, 2017; see also work on frontal involvement in "retrieval mode", Tulving, 1983;Lepage, Ghaffar, Nyberg, & Tulving, 2000;Tarder-Stoll, Jayakumar, Dimsdale-Zucker, Günseli, & Aly, 2020). The data from the current study, and from that of McCormick et al (2020) suggest that the temporal sequence of PFC-hippocampal activations can vary by the age of the memory and by reminders, but the underlying factors that influence it have yet to be determined.…”
Section: Neuroimaging Resultsmentioning
confidence: 99%
“…Past studies have suggested that either cholinergic (2729, 3537, 60) or dopaminergic (16, 24, 61) modulation could regulate hippocampal function after prediction errors, such as by enhancing plasticity and switching between processing modes. However, mixed evidence supporting both hypotheses has left the question unresolved (25, 26, 31, 33, 34). Here, we investigated whether activation of the basal forebrain or the VTA could explain the relationship between hippocampal activation after prediction error and subsequent memory.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested that either cholinergic (27-29, 41-43, 52) or dopaminergic (16,24,53) modulation could regulate hippocampal processing after prediction errors. However, mixed evidence supporting both hypotheses has left the question unresolved (25,26,31,37,40).…”
Section: Basal Forebrain Activation Relates To Hippocampal Processingmentioning
confidence: 99%
See 2 more Smart Citations